Oxford international lower seconadary english workbook 1 for grade 6 - Barber, Alison (Karachi: Oxford University Press., 2022)
The Oxford International Lower Secondary English: Workbook 1 for Grade 6 provides complementary exercises that reinforce the language skills and concepts introduced in the Student Book. Through a variety of practical tasks, students focus on improving reading comprehension, grammar, punctuation, and vocabulary. The workbook encourages independent learning with activities that promote critical thinking, creativity, and application of language skills in different contexts. It also helps students practice writing techniques such as descriptive, narrative, and persuasive writing, making it an essential tool for building a solid foundation in English and preparing for more advanced studies.